Preparation method of organic sulfur copolymer electrode material
By growing ferrocene-based MOFs on MXene nanosheets and copolymerizing with sulfur to form MXene@ferrocene-based MOFs-sulfur copolymer, the problems of polysulfide shuttle effect and slow reaction kinetics in lithium sulfur batteries are solved, and a composite material with high conductivity and high catalytic activity is achieved, which improves the performance of lithium sulfur batteries.
Patent Information
- Application Number
- CN202510412324.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-07-04
AI Technical Summary
There are problems in lithium-sulfur batteries with shuttle effect of soluble polysulfides and slow reaction kinetics of sulfur species, resulting in battery capacity decay, self-discharge and cycle stability.
Ferrocene-based MOFs were grown on MXene nanosheets by hydrothermal method, and then sulfur and ferrocene-based MOFs were copolymerized by reverse vulcanization reaction to form MXene@ferrocene-based MOFs-sulfur copolymer, and a composite material with high conductivity and high catalytic activity was constructed.
The discharge specific capacity and cycle stability of lithium sulfur batteries have been significantly improved. The initial discharge specific capacity at 0.2C ratio reaches 1335mAh g-1, and the specific capacity at 5C ratio is about twice that of ferrocene-based MOFs-sulfur copolymer, and the cycle life is also significantly improved.
Smart Images

Figure CN120261570A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy materials, and particularly relates to a preparation method of an organic sulfur copolymer electrode material and its application in the field of lithium-sulfur batteries. Background Art
[0002] Lithium-sulfur batteries are considered to be a promising next-generation energy storage system due to their high theoretical energy density, low cost of sulfur element, and environmental friendliness. However, the practical application of lithium-sulfur batteries still faces many challenges, mainly including the shuttle effect of soluble polysulfides and the slow reaction kinetics of sulfur species. These problems lead to fast battery capacity decay, serious self-discharge, low energy efficiency, and poor cycle stability. Using organic sulfur copolymers as the sulfur cathode is an effective method to solve the above problems. Li et al. (Li M, Wang Y, Sun S, Yang Y, Gu G, Zhang Z. Rational design of an allyl-rich triazine-based covalent organic framework host used as efficient cathode materials for Li-S batteries. Chem. Eng. J, 2022, 429: 132254.) reported a covalent organic framework material-sulfur copolymer material as the cathode of a lithium-sulfur battery. Due to the high specific surface area and adjustable pore structure of the covalent organic framework material, the shuttle effect of soluble polysulfides can be effectively inhibited. The initial discharge specific capacity of the lithium-sulfur battery using this cathode material is 991 mAh g -1 at a rate of 1C (1C = 1675 mAh g -1 , and after 1000 cycles, its discharge specific capacity still remains at 636 mAh g -1 . However, the covalent organic framework material itself has poor conductivity, and the redox kinetics of polysulfides is slow, which limits its performance under high sulfur loading conditions. Therefore, designing and synthesizing a new type of nanocomposite with both high conductivity and high catalytic activity to copolymerize with sulfur as the cathode of a lithium-sulfur battery is the key to realizing high-performance lithium-sulfur batteries.
[0003] As a kind of crystalline porous material, metal-organic frameworks (MOFs) are self-assembled from metal ions or metal clusters and organic ligands, with adjustable pore sizes, abundant chemical adsorption sites and high porosity, which can effectively inhibit the shuttle of polysulfides. In addition, through the rational design of organic ligands in the MOF framework, its copolymerization with sulfur can be realized. Two-dimensional transition metal carbides / nitrides (MXene) have high conductivity, strong polarity and excellent catalytic performance, and have attracted much attention in the research of lithium-sulfur batteries. Due to the good compatibility between MXene and MOFs, the heterostructure constructed by the two can form a strong interfacial effect and built-in electric field, greatly promoting electron transfer and significantly improving the conductivity of the composite material. However, due to the lack of catalytic ability of MOFs for the conversion of polysulfides, the redox kinetics of sulfur species is slow, seriously hindering the rate performance, cycle life and actual energy density of lithium-sulfur batteries. At present, the organic sulfur copolymer of MXene and ferrocene-based MOFs composite materials has not been reported. Therefore, the development of MXene@ferrocene-based MOFs-sulfur copolymer with high catalytic activity, strong conductivity, simple preparation and low cost is crucial for expanding the application of organic sulfur copolymer electrode materials in lithium-sulfur batteries. Summary of the Invention
[0004] The present invention mainly aims at the problems existing in the cathode materials of current lithium-sulfur batteries, and provides a preparation method of an organic sulfur copolymer electrode material. This method uses hydrothermal method to grow ferrocene-based MOFs on MXene nanosheets, and then makes sulfur copolymerize with ferrocene-based MOFs through inverse vulcanization reaction to obtain MXene@ferrocene-based MOFs-sulfur copolymer. The MXene@ferrocene-based MOFs-sulfur copolymer obtained in the present invention as the cathode material of lithium-sulfur batteries solves the problem of lack of catalytic active sites of MOFs, promotes electron transfer and lithium ion transport of the organic sulfur copolymer cathode; the battery assembled with this electrode material has a discharge specific capacity at a rate of 5C about twice that of the battery assembled with the ferrocene-based MOFs-sulfur copolymer electrode alone.
[0005] The technical solution of the present invention is as follows:
[0006] A preparation method of an organic sulfur copolymer electrode material, the method comprising the following steps:
[0007] (1) Synthesis of MXene powder
[0008] Add lithium fluoride and inorganic acid into a polytetrafluoroethylene container, and continuously stir until the lithium fluoride dissolves; then, under ice bath conditions, add the ternary layered carbonitride within 5 - 10 minutes; then transfer it to a constant temperature water bath at 30 - 50 °C and continuously stir for 18 - 32 hours; centrifuge and wash the obtained mixture until the pH value of the supernatant reaches neutral; finally, disperse the obtained black precipitate in deionized water and ultrasonically exfoliate it for 1 - 3 hours under nitrogen protection; then centrifuge at a speed of 3000 - 5000 rmp for 10 - 30 minutes, collect the dark upper liquid, and obtain MXene powder through freeze-drying for 3 - 5 days;
[0009] Among them, the mass ratio of lithium fluoride to the ternary layered carbonitride is 1:1 - 5; 10 - 30 mL of inorganic acid is added per 1 g of lithium fluoride; 50 - 100 mL of deionized water is added to the black precipitate obtained per 1 g of the ternary layered carbonitride;
[0010] (2) Synthesis of MXene@ferrocene-based MOFs
[0011] Add MXene powder, 1,1'-ferrocenedicarboxylic acid, N,N-dimethylformamide, metal salt and deionized water into a stainless steel autoclave with a polytetrafluoroethylene inner liner, and ultrasonically treat the obtained mixture for 10 - 60 minutes; heat the sealed autoclave to 100 - 150 °C, keep it for 6 - 18 hours, then cool it to room temperature and filter, wash the filter cake with deionized water and ethanol, and then vacuum dry it at a temperature of 40 - 80 °C for 18 - 32 hours to obtain MXene@ferrocene-based MOFs;
[0012] Among them, the mass ratio of MXene to 1,1'-ferrocenedicarboxylic acid is 1:5 - 15; the molar ratio of 1,1'-ferrocenedicarboxylic acid to the metal salt is 1:1 - 3; and, 0.1 - 0.2 mmol of metal salt is added per 20 mL of N,N-dimethylformamide; the volume ratio of deionized water to N,N-dimethylformamide is 1:1 - 4;
[0013] (3) MXene@ferrocene-based MOFs-sulfur copolymer
[0014] Uniformly mix MXene@ferrocene-based MOFs and sublimed sulfur, and transfer them to an autoclave with a polytetrafluoroethylene inner liner under an argon atmosphere; heat the sealed autoclave to 140 - 180 °C at a heating rate of 1 - 3 °C / min and keep it for 5 - 15 hours, then continue to heat it to 200 - 250 °C and keep it for 3 - 9 hours; after the reaction is completed, let the autoclave cool to room temperature naturally; heat the obtained product to 200 - 250 °C at a heating rate of 1 - 3 °C / min under a nitrogen atmosphere and keep it for 1 - 3 hours. Obtain MXene@ferrocene-based MOFs-sulfur copolymer.
[0015] Among them, the mass ratio of sublimed sulfur to MXene@ferrocene-based MOFs is 1:4 to 6;
[0016] The inorganic acid described in step (1) is hydrochloric acid, acetic acid, nitric acid or sulfuric acid;
[0017] The ternary layered carbonitride described in step (1) is Ti3SiC2, Ti3AlC2, Cr2AlC, V2AlC, Nb2AlC or Ta2AlC;
[0018] The metal salt described in step (2) is ferric chloride, nickel chloride, cadmium chloride, cobalt chloride, zinc chloride or manganese chloride.
[0019] The application of the organic sulfur copolymer electrode material obtained by the method is used as the positive electrode of a lithium-sulfur battery.
[0020] For the lithium-sulfur battery, the positive electrode is an aluminum foil loaded with the organic sulfur copolymer electrode material, and a polypropylene separator is used; the negative electrode is a lithium sheet; the electrolyte is a mixed solvent of 1,3-dioxolane and dimethyl ether (volume ratio 1:1) containing 1.0 mol / L lithium bis(trifluoromethanesulfonyl)imide;
[0021] The preparation method of the positive electrode of the lithium-sulfur battery described above includes the following steps: grinding the organic sulfur copolymer electrode material, conductive carbon black and polyvinylidene fluoride for 1 to 3 hours to obtain a mixture, then dropping N-methylpyrrolidone into it and stirring for 6 to 8 hours, coating the obtained slurry on the aluminum foil, drying the coated aluminum foil at a temperature of 40 to 80 °C for 18 to 32 hours, and cutting to obtain the positive electrode sheet of the lithium-sulfur battery, with 1 to 2 mg of the organic sulfur copolymer electrode material loaded per square centimeter of the positive electrode sheet;
[0022] The mass ratio of the organic sulfur copolymer electrode material, conductive carbon black and polyvinylidene fluoride is 6 to 8:1:1; 1 to 5 mL of N-methylpyrrolidone is dropped per 200 mg of the mixture,
[0023] The beneficial effects of the present invention are:
[0024] (1) The present invention provides a preparation method of an organic sulfur copolymer electrode material. The unsaturated carbon sites of the cyclopentadienyl units in the ferrocene structure can react with sulfur to form a cross-linked ferrocene-sulfur copolymer. At the same time, the customizable framework of ferrocene-based MOFs\MXene and the heterostructure of ferrocene-based MOFs are beneficial to the uniform dispersion of sulfur elements.
[0025] (2) In the structure of the organosulfur copolymer electrode material provided by the present invention, ferrocene serves as a copolymerization motif of sulfur, which can effectively alleviate the insulation of sulfur. Ferrocene-based MOFs provide a catalytic platform for the conversion of anchored long-chain polysulfide lithium, inhibiting the dissolution and shuttling of polysulfides. In addition, the built-in electric field between MXene and ferrocene-based MOFs accelerates the electron transfer during cycling, thereby promoting the reaction kinetics of sulfur species and further inhibiting the polysulfide shuttle effect.
[0026] (3) The battery assembled with the organosulfur copolymer electrode material provided by the present invention exhibits an initial discharge specific capacity of 1335 mAh g -1 at a rate of 0.2C, and the discharge specific capacity at a rate of 5C is approximately twice that of the battery assembled with the ferrocene-based MOFs-sulfur copolymer electrode. Brief Description of the Drawings
[0027] Figure 1 It is a schematic diagram for the preparation of the Ti3C2@NiFc-S composite material in Example 1.
[0028] Figure 2 It is a scanning electron microscope image of the Ti3C2@NiFc-S composite material in Example 1.
[0029] Figure 3 It is a rate performance graph of the Ti3C2@NiFc-S positive electrode in Example 1 and the NiFc-S positive electrode in Comparative Example 1.
[0030] Figure 4 It is a cycling test graph of the Ti3C2@NiFc-S positive electrode in Example 1 and the NiFc-S positive electrode in Comparative Example 1. Specific Embodiments
[0031] For a further understanding of the method of the present invention, specific descriptions are made in the form of examples in combination with the accompanying drawings. The following examples are only for the specific preparation method of the present invention and do not limit the scope of the present invention.
[0032] Comparative Example 1
[0033] (1) Synthesis of NiFc
[0034] Nickel chloride (8.1 mg, 0.0625 mmol) and 1,1'-ferrocenedicarboxylic acid (17.1 mg, 0.0625 mmol) were added to a stainless-steel autoclave with a polytetrafluoroethylene liner. 5 mL of deionized water and 10 mL of N,N-dimethylformamide were added to the autoclave, and ultrasonic treatment was carried out for 10 minutes to fully dissolve the solute. After the sealed autoclave was heated at 125 °C for 12 hours, it was naturally cooled to room temperature and then filtered. The filter cake was washed with deionized water and ethanol, and then dried in a vacuum oven at 60 °C for 24 hours to obtain a solid powder sample NiFc.
[0035] (2) Synthesis of NiFc-S
[0036] NiFc and sublimed sulfur were mixed at a weight ratio of 1:5 and transferred to a polytetrafluoroethylene-lined autoclave under an argon atmosphere. The sealed autoclave was heated to 160 °C at a heating rate of 1 °C / min and held for 10 hours, and then continued to be heated to 200 °C and heated for 6 hours. The obtained product was heated to 200 °C at a heating rate of 1 °C / min under a nitrogen atmosphere and held for 2 hours to remove the unreacted sulfur, and then a solid powder sample NiFc-S was obtained.
[0037] Example 1
[0038] (1) Synthesis of Ti3C2
[0039] Lithium fluoride (1 g) was placed in a 100 mL polytetrafluoroethylene beaker, and concentrated hydrochloric acid (20 mL, 9 mol / L) was slowly added under stirring until lithium fluoride was completely dissolved. Under an ice bath condition, Ti3AlC2 (1 g) was added to the beaker within 10 minutes. The beaker was placed in a 40 °C constant temperature water bath and continuously stirred for 24 hours to allow it to react fully. The mixture was collected and subjected to centrifugal washing until the pH value of the solution reached neutral. The black precipitate obtained above was dispersed in 100 mL of deionized water and ultrasonically exfoliated for 2 hours under nitrogen protection, and then centrifuged at 3500 rmp for 10 minutes, and the dark upper liquid was collected and freeze-dried for 4 days to obtain Ti3C2 powder.
[0040] (2) Synthesis of Ti3C2@NiFc
[0041] Ti3C2 powder (2 mg), nickel chloride (8.1 mg, 0.0625 mmol), and 1,1'-ferrocenedicarboxylic acid (17.1 mg, 0.0625 mmol) were added into a stainless-steel autoclave with a polytetrafluoroethylene liner. 5 mL of deionized water and 10 mL of N,N-dimethylformamide were added into the autoclave, and ultrasonically treated for 10 minutes to fully dissolve the solutes. After the sealed autoclave was heated at 125 °C for 12 hours, it was naturally cooled to room temperature and then filtered. The filter cake was washed with deionized water and ethanol, and then dried in a vacuum oven at 60 °C for 24 hours to obtain the solid powder sample Ti3C2@NiFc.
[0042] (3) Synthesis of Ti3C2@NiFc-S
[0043] Ti3C2@NiFc and sublimed sulfur were mixed at a weight ratio of 1:5 and transferred into a polytetrafluoroethylene-lined autoclave under an argon atmosphere. After the sealed autoclave was heated to 160 °C at a heating rate of 1 °C / min and held for 10 hours, it was further heated to 200 °C and heated for 6 hours. The obtained product was heated to 200 °C at a heating rate of 1 °C / min under a nitrogen atmosphere and held for 2 hours to remove the unreacted sulfur, and then the solid powder sample Ti3C2@NiFc-S was obtained.
[0044] Figure 1 In, the schematic diagram of the preparation of the Ti3C2@NiFc-S composite material in Example 1 of the present invention.
[0045] Figure 2 In, the scanning electron microscopy (TESCAN MIRALMS) was used to obtain the scanning electron micrograph of the Ti3C2@NiFc-S composite material in Example 1 of the present invention. The NiFc nanosheets were evenly distributed on the surface of Ti3C2, and no obvious granular structure was observed on the surface of the NiFc nanosheets, indicating that the sulfur copolymer was uniformly coated on the NiFc nanosheets, which confirmed the successful synthesis of the Ti3C2@NiFc-S composite material.
[0046] Figure 3 In, the lithium-sulfur battery assembled with the Ti3C2@NiFc-S cathode in Example 1 of the present invention could obtain an initial discharge specific capacity of 1335 mA h g -1 and still could obtain a high specific capacity of 640 mA h g -1 at 5C. In contrast, the initial discharge specific capacity of the NiFc-S cathode in Comparative Example 1 was only 1095 mA h g -1 under the condition of 0.2C, and it only showed 240 mAh g -1Specific capacity. It shows that the MXene and ferrocene-based MOF array structures have more excellent redox kinetics, inhibit the shuttle effect of polysulfides, and thus improve the performance of lithium-sulfur batteries.
[0047] Figure 4 Among them, for the lithium-sulfur battery assembled with the Ti3C2@NiFc-S cathode in Example 1 of the present invention, the average capacity decay per cycle after 1000 cycles at 1C is only 0.017%, while for the lithium-sulfur battery with the NiFc-S cathode in Comparative Example 1, the average capacity decay per cycle is as high as 0.07%. It shows that the MXene and ferrocene-based MOF array structures significantly improve the cycling stability of the organic sulfur copolymer electrode.
[0048] All battery performance tests assembled in the present invention were completed in a Neware battery test cabinet BST-5V 20mA. This test provides the capacity, rate performance, cycling stability and Coulomb efficiency of the battery. The voltage test range is from 1.7 to 2.8V, which can be adjusted as needed, and the temperature is maintained at 25°C.
[0049] Example 2
[0050] (1) Synthesis of Cr2C
[0051] Put lithium fluoride (1 g) into a 100 mL polytetrafluoroethylene beaker, and slowly add concentrated sulfuric acid (20 mL, 9 mol / L) under stirring until the lithium fluoride is completely dissolved. Add Cr2AlC (1 g) to the beaker within 10 minutes under ice bath conditions. Place the beaker in a 40°C constant temperature water bath and stir continuously for 24 hours to allow full reaction. Collect the mixture and perform centrifugal washing until the pH value of the solution reaches neutral. Disperse the obtained black precipitate in 100 mL of deionized water, ultrasonically exfoliate it for 2 hours under nitrogen protection, then centrifuge it at 3500 rmp for 10 minutes, collect the dark upper liquid, and obtain Cr2C powder through freeze-drying for 4 days.
[0052] (2) Synthesis of Cr2C@CoFc
[0053] Add Cr2C powder (2 mg), cobalt chloride (8.1 mg, 0.0625 mmol), and 1,1'-ferrocenedicarboxylic acid (17.1 mg, 0.0625 mmol) into a stainless steel autoclave with a polytetrafluoroethylene liner. Add 5 mL of deionized water and 10 mL of N,N-dimethylformamide to the autoclave, and ultrasonically treat for 10 minutes to fully dissolve the solute. Place the sealed autoclave in an oven at 125°C and heat for 12 hours, then naturally cool to room temperature and filter. Wash the filter cake with deionized water and ethanol, and then dry it in a 60°C vacuum oven for 24 hours to obtain a solid powder sample Cr2C@CoFc.
[0054] (3) Synthesis of Cr2C@CoFc-S
[0055] Cr2C@CoFc and sublimed sulfur were mixed at a weight ratio of 1:5 and transferred to a PTFE-lined autoclave under an argon atmosphere. After the sealed autoclave was heated to 160 °C at a heating rate of 1 °C / min and held for 10 hours, it was further heated to 200 °C and heated for 6 hours. The obtained product was heated to 200 °C at a heating rate of 1 °C / min under a nitrogen atmosphere and held for 2 hours to remove the unreacted sulfur, and then a solid powder sample Cr2C@CoFc-S was obtained.
[0056] Example 3
[0057] (1) Synthesis of V2C
[0058] Lithium fluoride (1 g) was placed in a 100 mL PTFE beaker, and concentrated nitric acid (20 mL, 9 mol / L) was slowly added under stirring until the lithium fluoride was completely dissolved. Under an ice bath condition, V2AlC (1 g) was added to the beaker within 10 minutes. The beaker was placed in a 40 °C constant temperature water bath and stirred continuously for 24 hours to allow sufficient reaction. The mixture was collected and subjected to centrifugal washing until the pH value of the solution reached neutral. The black precipitate obtained above was dispersed in 100 mL of deionized water and ultrasonically exfoliated for 2 hours under nitrogen protection, and then centrifuged at 3500 rmp for 10 minutes. The dark upper layer liquid was collected and freeze-dried for 4 days to obtain V2C powder.
[0059] (2) Synthesis of V2C@ZnFc
[0060] V2C powder (2 mg), zinc chloride (8.5 mg, 0.0625 mmol) and 1,1'-ferrocenedicarboxylic acid (17.1 mg, 0.0625 mmol) were added to a stainless steel autoclave with a PTFE lining. 5 mL of deionized water and 10 mL of N,N-dimethylformamide were added to the autoclave, and ultrasonically treated for 10 minutes to dissolve the solute sufficiently. After the sealed autoclave was heated at 125 °C for 12 hours, it was naturally cooled to room temperature and then filtered. The filter cake was washed with deionized water and ethanol, and then dried in a 60 °C vacuum oven for 24 hours to obtain a solid powder sample V2C@ZnFc.
[0061] (3) Synthesis of V2C@ZnFc-S
[0062] V2C@ZnFc and sublimed sulfur were mixed at a weight ratio of 1:5 and transferred to a polytetrafluoroethylene-lined autoclave under an argon atmosphere. After the sealed autoclave was heated to 160 °C at a heating rate of 1 °C / min and held for 10 hours, it was further heated to 200 °C and heated for 6 hours. The obtained product was heated to 200 °C at a heating rate of 1 °C / min under a nitrogen atmosphere and held for 2 hours to remove unreacted sulfur, and then a solid powder sample V2C@ZnFc-S was obtained.
[0063] Example 4
[0064] The Ti3C2@NiFc-S composite material prepared in Example 1 was used as the positive electrode and applied to a lithium-sulfur battery.
[0065] (1) Preparation of the Ti3C2@NiFc-S positive electrode:
[0066] 160 mg of the Ti3C2@NiFc-S composite material, 20 mg of conductive carbon black, and 20 mg of polyvinylidene fluoride were added to a mortar and ground for 2 hours to fully mix the three. After dropping 3 mL of N-methylpyrrolidone, it was stirred for 8 hours to make a slurry, which was coated on the surface of aluminum foil and dried at 60 °C for 24 hours, and then cut into a circular positive electrode with a diameter of 14 mm using a slicing machine. The positive electrode sheet was loaded with 1.4 mg of the Ti3C2@NiFc-S composite material per square centimeter.
[0067] (2) Assembly of the battery:
[0068] The lithium-sulfur battery used the aluminum foil loaded with the Ti3C2@NiFc-S composite material as the positive electrode; a polypropylene separator was used; a lithium sheet was used as the negative electrode; the electrolyte was a mixed solution of 1,3-dioxolane and dimethyl ether (volume ratio 1:1) containing 1.0 mol / L lithium bis(trifluoromethanesulfonyl)imide, and a button-type lithium-sulfur battery was assembled in a glove box filled with argon.
[0069] Matters not covered by this invention are well-known technologies.
Claims
1. A preparation method of an organic sulfur copolymer electrode material, characterized in that, The method includes the following steps: (1) Synthesis of MXene powder Add lithium fluoride and inorganic acid into a polytetrafluoroethylene container, and continuously stir until lithium fluoride dissolves; subsequently, under ice bath conditions, add ternary layered carbonitride within 5 - 10 minutes; then transfer it to a constant temperature water bath at 30 - 50 °C and continuously stir for 18 - 32 hours; centrifuge and wash the obtained mixture until the pH value of the supernatant reaches neutral; finally, disperse the obtained black precipitate in deionized water and ultrasonically exfoliate it for 1 - 3 hours under nitrogen protection; then centrifuge at a speed of 3000 - 5000 rmp for 10 - 30 minutes, collect the dark upper liquid, and obtain MXene powder through freeze-drying for 3 - 5 days; Among them, the mass ratio of lithium fluoride to ternary layered carbonitride is 1:1 - 5; 10 - 30 mL of inorganic acid is added per 1 g of lithium fluoride; 50 - 100 mL of deionized water is added to the black precipitate obtained per 1 g of ternary layered carbonitride; (2) Synthesis of MXene@ferrocene-based MOFs Add MXene powder, 1,1'-ferrocenedicarboxylic acid, N,N-dimethylformamide, metal salt, and deionized water into a stainless-steel autoclave with a polytetrafluoroethylene liner, and ultrasonically treat the obtained mixture for 10 - 60 minutes; heat the sealed autoclave to 100 - 150 °C, keep it for 6 - 18 hours, then cool it to room temperature and filter, wash the filter cake with deionized water and ethanol, and then vacuum dry it at a temperature of 40 - 80 °C for 18 - 32 hours to obtain MXene@ferrocene-based MOFs; Among them, the mass ratio of MXene to 1,1'-ferrocenedicarboxylic acid is 1:5 - 15; the molar ratio of 1,1'-ferrocenedicarboxylic acid to metal salt is 1:1 - 3; and, 0.1 - 0.2 mmol of metal salt is added per 20 mL of N,N-dimethylformamide; the volume ratio of deionized water to N,N-dimethylformamide is 1:1 - 4; (3) MXene@ferrocene-based MOFs-sulfur copolymer Uniformly mix MXene@ferrocene-based MOFs and sublimed sulfur, and transfer them to a stainless-steel autoclave with a polytetrafluoroethylene liner under an argon atmosphere; heat the sealed autoclave at a heating rate of 1 - 3 °C / min to 140 - 180 °C and keep it for 5 - 15 hours, then continue to heat it to 200 - 250 °C and keep it for 3 - 9 hours; after the reaction ends, let the autoclave cool to room temperature naturally; heat the obtained product to 200 - 250 °C at a heating rate of 1 - 3 °C / min under a nitrogen atmosphere and keep it for 1 - 3 hours to obtain MXene@ferrocene-based MOFs-sulfur copolymer; Among them, the mass ratio of sublimed sulfur to MXene@ferrocene-based MOFs is 1:4 - 6.
2. The preparation method of the organic sulfur copolymer electrode material according to claim 1, characterized in that, The ternary layered carbonitride described in step (1) is Ti3SiC2, Ti3AlC2, Cr2AlC, V2AlC, Nb2AlC, or Ta2AlC.
3. The preparation method of the organic sulfur copolymer electrode material according to claim 1, characterized in that, The inorganic acid described in step (1) is hydrochloric acid, acetic acid, nitric acid, or sulfuric acid.
4. The preparation method of the organic sulfur copolymer electrode material according to claim 1, characterized in that, The metal salt described in step (2) is ferric chloride, nickel chloride, cadmium chloride, cobalt chloride, zinc chloride or manganese chloride.
5. Use of the organic sulfur copolymer electrode material obtained by the method according to claim 1, characterized in that, It is used as the positive electrode of a lithium-sulfur battery.
6. The application according to claim 5, characterized in that, For the lithium-sulfur battery, the positive electrode is an aluminum foil loaded with an organic sulfur copolymer electrode material, and a polypropylene separator is used; the negative electrode is a lithium sheet; the electrolyte is a mixed solvent of 1,3-dioxolane and dimethyl ether (volume ratio 1:1) containing 1.0 mol / L lithium bis(trifluoromethanesulfonyl)imide. The preparation method of the positive electrode of the lithium-sulfur battery described above includes the following steps: grinding the organic sulfur copolymer electrode material, conductive carbon black and polyvinylidene fluoride for 1 to 3 hours to obtain a mixture, then dropping N-methylpyrrolidone into it and stirring for 6 to 8 hours, coating the obtained slurry on the aluminum foil and drying it at a temperature of 40 to 80 °C for 18 to 32 hours, and cutting to obtain the positive electrode sheet of the lithium-sulfur battery, with 1 to 2 mg of the organic sulfur copolymer electrode material loaded per square centimeter of the positive electrode sheet. The mass ratio of the organic sulfur copolymer electrode material, conductive carbon black and polyvinylidene fluoride is 6 to 8:1:1; 1 to 5 mL of N-methylpyrrolidone is dropped per 200 mg of the mixture.